Risk Factors and Patterns of Locoregional Recurrence after Radical Nephrectomy for Locally Advanced Renal Cell Carcinoma - Yoo, Gyu Sang; Park, Won; Pyo, Hongryull; Jeong, Byong Chang; Jeon, Hwang Gyun; Kang, Minyong; Seo, Seong Il; Jeon, Seong Soo; Lee, Hyun Moo; Choi, Han Yong; Park, Byung Kwan; Kim, Chan Kyo; et al. (Cancer research and treatment, 2022)
Purpose We aimed to investigate the risk factors and patterns of locoregional recurrence (LRR) after radical nephrectomy (RN) in patients with locally advanced renal cell carcinoma (RCC).Materials and Methods We retrospectively analyzed 245 patients who underwent RN for non-metastatic pT3-4 RCC from January 2006 to January 2016. We analyzed the risk factors associated with poor locoregional control using Cox regression. Anatomical mapping was performed on reference computed tomography scans showing intact kidneys.Results The median follow-up duration was 56 months (range, 1 to 128 months). Tumor extension to renal vessels or the inferior vena cava (IVC) and Fuhrman’s nuclear grade IV were identified as independent risk factors of LRR. The 5-year actuarial LRR rates in groups with no risk factor, one risk factor, and two risk factors were 2.3%, 19.8%, and 30.8%, respectively (p < 0.001). The locations of LRR were distributed as follows: aortocaval area (n=2), paraaortic area (n=4), retrocaval area (n=5), and tumor bed (n=11). No LRR was observed above the celiac axis (CA) or under the inferior mesenteric artery (IMA).Conclusion Tumor extension to renal vessels or the IVC and Fuhrman’s nuclear grade IV were the independent risk factors associated with LRR after RN for pT3-4 RCC. The locations of LRR after RN for RCC were distributed in the tumor bed and regional lymphatic area from the bifurcation of the CA to that of the IMA.